1999
DOI: 10.1103/physrevb.59.8436
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle spectrum of a type-II superconductor in a high magnetic field with randomly pinned vortices

Abstract: We show that gapless superconductivity of a strongly type-II superconductor in a high magnetic field prevails in the presence of disorder, suggesting a topological nature. We calculate the density of states of the Bogoliubov-de Gennes quasi-particles for a two-dimensional inhomogeneous system in both cases of weak and strong disorder. In the limit of very weak disorder, the effect is very small and the density of states is not appreciably changed. As the disorder increases, the density of states at low energie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 17 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…In the gapped s-wave case, however, the disorder introduces states in the gap thereby changing qualitatively the low-energy density of states, as in the high-field limit. 10 We found a power-law behavior with an exponent that scales with the magnetic length. rϭ(3,14), (4,15), (5,16), (6,17), (7,18), (8,19) around a vortex position r v ϭ(5.5,16.5) belonging to a disordered vortex lattice.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the gapped s-wave case, however, the disorder introduces states in the gap thereby changing qualitatively the low-energy density of states, as in the high-field limit. 10 We found a power-law behavior with an exponent that scales with the magnetic length. rϭ(3,14), (4,15), (5,16), (6,17), (7,18), (8,19) around a vortex position r v ϭ(5.5,16.5) belonging to a disordered vortex lattice.…”
Section: Discussionmentioning
confidence: 96%
“…In the same regime of high magnetic fields, but with randomly pinned vortices and no impurities, the density of states at low energies increases significantly with respect to the lattice case suggesting a finite value at zero energy. 10 References 11 and 12 considered the effects of random and statistically independent scalar and vector potentials on d-wave quasiparticles and it was predicted 12 that at low energies (⑀)ϳ 0 ϩa⑀ 2 , where 0 ϳB 1/2 . The effect of randomly pinned discrete vortices on the spectrum of a d-wave superconductor was considered recently and a preliminary report was presented in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we build on the results of the previous section to study how the spectra in the 0 • and 45 • vortex-lattice orientations progressively become identical as disorder is increased. Unlike previous studies, 17,20 we consider positional disorder with respect to a perfect lattice rather than completely random vortex positions, and we focus on the vortex-core spectrum rather than the average DOS. Starting from the ideal lattices, we introduce a disorder δR = dρ(cos τ, sin τ) in the vortex positions, where d is the initial distance between vortices, ρ is a random number with Gaussian distribution of variance η, and τ is a uniform random number between 0 and 2π.…”
Section: Vortex-core Ldos In Disordered Vortex Latticesmentioning
confidence: 99%
“…10 Furthermore, it was shown that the high-field gapless character of the excitation spectrum is not destroyed by a moderate level of nonmagnetic impurities present in either dirty homogeneous superconductor 11 or dirty inhomogeneous superconducting systems. 12 The strongest evidence for Landau level quantization within the superconducting state comes from the experimental observation of de Haas-van Alphen ͑dHvA͒ oscillations in various A-15 and borocarbide superconductors. 3 The persistence of the dHvA signal deep within the mixed state of these three-dimensional extreme type-II systems can be attributed to the presence of a small portion of the Fermi surface containing gapless quasiparticle excitations, surrounded by regions where the gap is large.…”
mentioning
confidence: 99%
“…However, a marked difference appears at lower fields H ≪ 0.5H c2 , where an swave superconductor is clearly in the regime of localized, bound vortex core states while a d-wave system still exhibits the extended nature of low-lying quasiparticle excitations as predicted by Franz and Tešanović 10 . Furthermore, it was shown that the high-field gapless character of the excitation spectrum is not destroyed by a moderate level of nonmagnetic impurities present in either dirty homogeneous superconductor 11 or dirty inhomogeneous superconducting systems 12 .…”
mentioning
confidence: 99%